DIGITALISASI SERTIFIKAT TANAH MELALUI PROGRAM ELEKTRONIK BADAN PERTANAHAN NASIONAL: TANTANGAN DAN KEPASTIAN HUKUM DALAM SISTEM AGRARIA INDONESIA - Agustinus Luturmas; Odilo Dwi Suharto Fautngilyanan (PATRIOT, 2026)
Advancements in information technology have prompted the Indonesian government to undertake a digital transformation across various public service sectors—including land administration—through the implementation of electronic land certificates. This policy is part of an effort to modernize land administration to enhance service efficiency, strengthen legal certainty, and minimize issues prevalent in conventional land systems, such as document forgery, duplicate certificates, and "land mafia" activities. However, the implementation of electronic land certificates also raises concerns regarding data security, the evidentiary weight of electronic documents, and public readiness for this digital transformation. This study aims to analyze the legal framework governing the digitization of land certificates within Indonesia's agrarian system, examine implementation challenges regarding legal certainty and land data security, and formulate an ideal model for the legal protection of electronic land certificates in Indonesia's digital agrarian system. The study employs a normative legal research method utilizing statutory, conceptual, and cyber law approaches. Legal materials consist of primary sources (legislation) and secondary sources (books, academic journals, research findings, and relevant literature). A descriptive-qualitative analysis was conducted. The findings indicate that the digitization of land certificates rests on a robust legal foundation, supported by Law No. 5 of 1960 (Basic Agrarian Law), the Law on Electronic Information and Transactions, the Personal Data Protection Law, and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN) No. 1 of 2021 concerning Electronic Certificates. Nevertheless, implementation faces various challenges, including cybersecurity threats, public skepticism regarding the evidentiary value of electronic certificates, disparities in technology access, land data protection issues, and the adequacy of both legal and technological infrastructure. Therefore, a legal protection model is required that integrates regulatory strengthening, robust cybersecurity systems, land data protection aligned with the Personal Data Protection Law, a people-centric digitalization approach, and enhanced legal and digital literacy. This model is expected to create a secure and trustworthy digital land system that provides legal certainty for the public.